2017
DOI: 10.1038/cti.2016.91
|View full text |Cite
|
Sign up to set email alerts
|

Embracing the gut microbiota: the new frontier for inflammatory and infectious diseases

Abstract: The gut microbiota provides essential signals for the development and appropriate function of the immune system. Through this critical contribution to immune fitness, the gut microbiota has a key role in health and disease. Recent advances in the technological applications to study microbial communities and their functions have contributed to a rapid increase in host–microbiota research. Although it still remains difficult to define a so-called ‘normal' or ‘healthy' microbial composition, alterations in the gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
75
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(82 citation statements)
references
References 97 publications
(177 reference statements)
1
75
0
3
Order By: Relevance
“…Recent evidence in humans supports an etiological role for the intestinal microbiota in inflammatory atherosclerosis [18, 19]. The gastrointestinal tract is the largest reservoir of microbes in humans and is comprised of predominantly commensal bacteria [20, 21].…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence in humans supports an etiological role for the intestinal microbiota in inflammatory atherosclerosis [18, 19]. The gastrointestinal tract is the largest reservoir of microbes in humans and is comprised of predominantly commensal bacteria [20, 21].…”
Section: Introductionmentioning
confidence: 99%
“…Although the lifestyle and genetic factors are also considered as the influential determinants of obesity, recent research exploring physiological significance on the gut microbiota suggested it to be a key environmental factor that influences the metabolic syndrome [128,129]. Another striking feature of the gut microbiota is the heritability that links abundance of the specific gut microbial taxa to the host genetics [130] and amongst the heritable taxa, Firmicutes phylum is associated with leanness [47]. Composition of the gut microbiota is influenced by host genetics and can impact host metabolism [131].…”
Section: Metabolic Diseasesmentioning
confidence: 99%
“…Reduced gut microbial diversity has been reported to increase the risk of allergy in school children and in most of the cases, it is food allergy [142]. A recent study has shown that depletion of bacteria like Bifidobacterium, Akkermansia, and Faecalibacterium, along with an abundance of fungi such as Candida and Rhodotorula in neonates, may predispose to allergic susceptibility by influencing T-cell differentiation [47]. Furthermore, a study by the Canadian Healthy Infant Longitudinal Development (CHILD) identified a transient alteration in the gut microbiota associated with the reduced abundance of bacteria belonging to Lachnospira, Veillonella, Faecalibacterium and Rothia genera during the first 100 days of life in the infants found to increase the risk of asthma [46].…”
Section: Allergiesmentioning
confidence: 99%
See 1 more Smart Citation
“…If patients occasionally have taken overdose antibiotics, doctors just give them faeces from whom they live with to help rebuilt their gut microbiomes. As the technologies developed, we know gut microbiomes have changed if being obesity [1], being sick [2] or being ageing [3], so researchers tried to make faeces 'drugs' from thin, healthy and young individuals [4]. It's prospective and shows great benefits if this idea works in the near future, however, in this review, we' d like to discuss some other essential questions in this area.…”
Section: Introductionmentioning
confidence: 99%